2011
DOI: 10.3390/md9030387
|View full text |Cite
|
Sign up to set email alerts
|

Mycosporine-Like Amino Acids: Relevant Secondary Metabolites. Chemical and Ecological Aspects

Abstract: Taxonomically diverse marine, freshwater and terrestrial organisms have evolved the capacity to synthesize, accumulate and metabolize a variety of UV-absorbing substances called mycosporine-like amino acids (MAAs) as part of an overall strategy to diminish the direct and indirect damaging effects of environmental ultraviolet radiation (UVR). Whereas the enzymatic machinery to synthesize MAAs was probably inherited from cyanobacteria ancestors via the endosymbionts hypothesis, metazoans lack this biochemical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
313
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(343 citation statements)
references
References 256 publications
(870 reference statements)
10
313
0
4
Order By: Relevance
“…Compound 3 was supposed to be formed by the esterification between mycosporine glutamicol and ethanol, containing some acidic traces, during NaCl removal in the semi-purification step. Indeed, many MAAs can be converted to their methyl esters by treatment with HCl-methanol [1]. Comparison of the crude and the semi-purified aqueous extracts using HPLC-DAD-MS 2 analysis confirmed that compound 3 (R t = 15.75 min) was a by-product as only found in the semi-purified extract (l " Fig.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Compound 3 was supposed to be formed by the esterification between mycosporine glutamicol and ethanol, containing some acidic traces, during NaCl removal in the semi-purification step. Indeed, many MAAs can be converted to their methyl esters by treatment with HCl-methanol [1]. Comparison of the crude and the semi-purified aqueous extracts using HPLC-DAD-MS 2 analysis confirmed that compound 3 (R t = 15.75 min) was a by-product as only found in the semi-purified extract (l " Fig.…”
mentioning
confidence: 89%
“…Mycosporine-like compounds comprising mycosporines and MAAs have received much attention for their putative role in UV photoprotection as antioxidants and osmoprotectants [1][2][3][4]. Mycosporine-like compounds are small water-soluble molecules composed of cyclohexenone (oxo-mycosporine) or cyclohexenimine (imino-mycosporine) ring structures conjugated to an amino acid or an amino alcohol subunit.…”
Section: Introductionmentioning
confidence: 99%
“…Produksi rumput laut di seluruh Indonesia berasal dari budidaya, antara lain dikembangkan di Jawa, Bali, NTB, Sulawesi dan Maluku (Nur 2009). Rumput laut E. cottonii mengandung protein, lipid, karbohidrat, α tokoferol, mineral, vitamin C, dan vitamin E (Wandansari et al 2013;Pringgenies et al 2013), dapat mensintesis senyawa mycosporine (MAAs) yang berperan dalam absorpsi sinar UV (Carreto & Carignan 2011;Rosic & Dove 2011;Navarro 2015). Rumput laut digunakan dalam pembuatan kosmetik dalam bentuk karagenan, yaitu pada produk sabun (Hidayat 2006), losion (Erungan et al 2009;Razi 2009;Purwaningsih et al 2015), dan gel topikal (Wulandari 2012) serta dalam bentuk bubur rumput laut untuk krim tabir surya .…”
Section: Pendahuluanunclassified
“…Several marine organisms, notably photosynthetic organisms, produce UV-absorbing compounds such as scytonemins (cyanobacteria), mycosporines, mycosporine-like amino acids (MAAs), and carotenoids to protect themselves from UV radiation [66][67][68][69]. Moreover, despite their large contribution to marine biodiversity and biomass, the UV filters produced by microbial components have been poorly investigated.…”
Section: Active Ingredients For Topical Photoprotectionmentioning
confidence: 99%